Comparative cytotoxic and genotoxic effects of permethrin and its nanometric form on human erythrocytes and lymphocytes in vitro. (25th September 2016) - Sundaramoorthy, Rajiv; Velusamy, Yuvaraj; Balaji, A.P.B.; Mukherjee, Amitava; Chandrasekaran, Natarajan
Abstract: The research on the novel pesticides such as nanopesticides has become inevitable to control the mosquito population. Nanopermethrin (NP), one of such kind was formulated in pesticide loaded oil-in-water (o/w) microemulsion by rapid evaporation. Even though NP possess improved efficacy against the target pests, the toxicological investigation on the human or mammalian system remains unexplored. So, the present study focused on a comparative investigation of the cytotoxic and genotoxic effects of NP in vitro and its commercial parental bulk form of permethrin (BP) on human peripheral erythrocyte/lymphocyte by erythrocyte morphology analysis, cell viability assay, and cytokinesis-block micronucleus (CBMN) assay. The NP and BP concentrations (10, 25, 50 and 100 μg/ml) interacted with human blood cells, and the morphological changes were observed using a phase contrast microscope. The drastic increase of echinocyte was observed at 24, 48 and 72 h treatment as compared with the control. The cell viability studies have shown the significant decrease with increase in NP and BP concentration. CBMN study showed a series correlation in the number of micronuclei, bridge, bud, trinucleated and tetranucleated when interacted with different levels of NP and BP, as comparative to control *p < 0.05, **p < 0.001, ***p < 0.0001. Highlights: Permethrin nanopowder (NP) was formulated from pesticide loaded microemulsion. In vitro toxicity of NP and BP was evaluated on human lymphocytes and erythrocytes. Cytotoxicity and genotoxicity was proportional to concentration increment. Toxicological profile of NP was lesser comparative to BP.